EGYPT. AN UNKNOWN PORTCULLIS TYPE IS DISCOVERED IN THE BENT PYRAMID OF SNEFERU IN DUSHORE - A. M. Yaroschuk (Вестник Кемеровского государственного университета, 2016)
The article analyzes the design and operation of the portcullis blocking the corridor in the Bent Pyramid. It proves that the drawing of an activated portcullis demonstrated by D. Perring in 1939 is wrong. Egyptologists have been making references to the drawing for many years. The author concludes that a new type of portcullis was activated in the attempt of the robbers to enter the pyramid.